Orally bioavailable HCV NS5A inhibitors of unsymmetrical structural class. Issue 17 (1st September 2020) - Nakamura, Hiroshi; Fujioka, Shingo; Terui, Takashi; Okuda, Satoshi; Kondo, Kentaro; Tamatani, Yoshinori; Akagi, Yusuke; Komoda, Yasumasa; Kinoshita, Wataru; Ito, Soichiro; Maeda, Kimiya; Ukaji, Yutaka; et al.
Graphical abstract: Abstract: A novel unsymmetrical structural class of orally bioavailable hepatitis C virus (HCV) nonstructural 5A protein (NS5A) inhibitors has been generated by improving both the solubility and membrane permeability of the lead compound found in our previous work. The representative compound 14, with a 5-hydroxymethylpyrazine group and a 3- t -butylpropargyl group on each side of the molecule, exhibited the best oral bioavailability in this study, inhibiting not only the HCV genotype 1a, 1b, 2a, and 3a replicons with EC50 values in the picomolar range, but also inhibited 1a Q30 mutants induced by launched symmetrical inhibitors with EC50 values in the low nanomolar range.